An original approach to assess elastic properties of a short glass fibre reinforced thermoplastic combining X-ray tomography and finite element computation. (July 2015) - Ayadi, Abderrahmane; Nouri, Hedi; Guessasma, Sofiane; Roger, Frederic
Abstract: A large debate animates the community about the mechanical performance of complex parts obtained by injection moulding (IM) of short glass fibre reinforced polymer (SGFRP) composites. Difficulties to measure exact fibre length and orientation distributions in complex geometries are limiting in terms of basic understanding of damage mechanisms in industrial parts and fatigue design improvement. In this work, we are interested to shed more light on the mechanical performance of short glass fibre reinforced polyamide composites in correlation to local microstructural heterogeneities which are caused by inserts used during IM. For such purpose, we combine X-ray microtomography (μ-CT) and finite element computation to determine the elastic modulus in various positions in an open hole plate configuration with a dissymmetric fibre distribution. Our predictions show that effective properties do not vary significantly around the hole in all space directions. However, stress profiles (through the thickness) far enough from the hole reveal a five-layer quasi symmetric structure evolving to three-layer near the cylindrical insert. We believe that such alteration is responsible for the observed failure of the composite at precisely the positions of highly affected fibre distribution.